Comparative analysis of simulated in-situ colonization and degradation by Lentinula edodes on oak wafer and corn stalk - Mou, Chunye; Gong, Yuhua; Chen, Lianfu; Martin, Francis; Kang, Heng; Bian, Yinbing (Frontiers in Microbiology, 2023)
Introduction The depolymerization of lignocellulose biomass by white-rot fungi has been an important research topic. However, few simulated in-situ analyses have been conducted to uncover the decay. Methods In this study, the white-rot Lentinula edodes was used to colonize the wood and non-wood substrates, and then hyphal transcriptional response and substrate degradation were analyzed during the spatial-temporal colonization on different type substrates to better understand the depolymerization of lignocellulose. Results and discussion Faster growth and thicker mat of hyphae on corn stalk were observed in comparison to oak wafer. Coincide with the higher levels of gene transcripts related to protein synthesis on corn stalk. The higher lignin oxidase activity of hyphae was detected on oak wafer, and the higher cellulase activity was observed on corn stalk containing a much higher content of soluble sugars. A large number of carbohydrate-binding module (CBM1 and CBM20)-containing enzyme genes, including lytic polysaccharide monooxygenase (AA9), cellobiohydrolase (GH6 and GH7), glucanase (GH5), xylanase (GH10 and GH11), glucoamylase (GH15), and alpha-amylase (GH13), were significantly upregulated in the back-distal hyphae colonized on corn stalk. The hyphae tended to colonize and degrade the secondary cell wall, and the deposited oxalate crystal suggested that oxalate may play an important role during lignocellulose degradation. In addition, lignin was degraded in priority in oak wafer. Of note, three lignin monomers were degraded simultaneously in oak wafer but sequentially in corn stalk. This growth Our results indicated that the white-rot degradation pattern of lignocellulose is determined by the chemical composition and structure of the colonized biomass.